2018
DOI: 10.1088/1755-1315/105/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste heat from separation process of Ulubelu’s geothermal power plant by implementing an Absorption Refrigeration System (ARS) to improve plant performance

Abstract: Abstract. Utilization of geothermal energy for water-dominated reservoir usually involves a separation process that turns geothermal fluid mixtures into pure steam and brine water. This process also occurred on Ulubelu's geothermal power plant (GPP). As waste energy from the power generation process, the remaining heat energy in brine water is still high enough to run an absorption refrigeration system (ARS). This study proposed an integrated power generation and absorption system that operate side by side for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The cost of other major components, such as the turbine and pump, is estimated based on power capacity. The purchase equipment cost (PEC) for each component in geothermal polygeneration system was calculated using the following formula 43,49) :…”
Section: Economic and Cost Analysis Of The Systemmentioning
confidence: 99%
“…The cost of other major components, such as the turbine and pump, is estimated based on power capacity. The purchase equipment cost (PEC) for each component in geothermal polygeneration system was calculated using the following formula 43,49) :…”
Section: Economic and Cost Analysis Of The Systemmentioning
confidence: 99%
“…It was concluded that the integrated energy and absorption system could not meet the viability requirements because it requires a large cooling capacity, increasing the total investment cost. Nasruddin and Wibowo (2018) carry out an analysis of an integrated energy generation and absorption cooling system through the use of residual heat from the separation process of a geothermal power plant, and the implementation of an absorption cooling system, to improve the plant performance. Optimal values were identified to minimize energy efficiency and the annual cost for the integrated system.…”
Section: Introductionmentioning
confidence: 99%